Corporate sponsored image films - Bennett, James R. (1983)
The vast number of high quality corporate image and advocacy films, combined with the many other instruments of persuasion and control by corporations, powerfully direct the attitudes of the populace. In the absence of equal access, the best protection against deception from any powerful institution is skepticism — minds trained in critical thinking. But technically proficient, expensive films (costing from $50,00 to $600,000) encourage credulity instead of thought. The schools should train young people, therefore, how to resist corporate film propaganda by teaching them the kinds of questions to ask. An analysis of Chesebrough-Pond Corporation's Family offers an effective method through combining traditional rhetorical awareness of the speaker in a communication, knowledge of informal fallacies, the National Council of Teachers of English Committee on Public Doublespeak's ‘intensify/downplay’ approach, and Richard Ohmann's method in ‘Doublespeak and Ideology in Ads’.
Keywords: Vast Number; National Council; Critical Thinking; Young People; Economic Growth